Bimbingan Kelompok Menggunakan Teknik Diskusi Kelompok Untuk Mengurangi Kenakalan Remaja - Syamsiah, Siti; Pan Pangestie, Esty; Feronika, Nopi (Jurnal Bimbingan dan Konseling Pandohop, 2024)
Juvenile delinquency is the behavior of some teenagers that is contrary to law, religion and social norms. This research was conducted to determine whether the application of group guidance using group discussion techniques can reduce juvenile delinquency. This research is a Pre-Experimental Design research with One Group Pretest-Posttest Design type. Based on data, the experimental group was compared with the group before being provided with services. The average pre-test percentage of 10 subjects was 76%, including the high category, indicating that the level of juvenile delinquency is high. After being provided with the service, the post-test results for the 10 subjects decreased to 56% in the low category, which indicates that the level of juvenile delinquency is low or has decreased. Based on data analysis, it is known that the research significance is 0.00 < 0.05. It can be concluded that Ha is accepted and Ho is rejected. Where group guidance services using group discussion techniques can reduce juvenile delinquency in class VII SMPN 3 Palangka Raya. It is hoped that this research can become a reference for further research, thus adding to the insight of other researchers, especially those regarding student juvenile delinquency.